THE IMPORTANCE OF ENGLISH IN THE JOB MARKET (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2024)
This article examines the critical role of the English language in today’s job market. It discusses how English proficiency enhances employability, facilitates communication in multicultural workplaces, and fosters career advancement. The article encourages both job seekers and employers to recognize the value of English skills in achieving professional success.